Penerapan Hubungan Kerja dan Perjanjian Kerja Waktu Tertentu (PKWT) pada Perusahaan Migas - Nelson, Alden; Nurhidayati, Mualifah; Fitri Riana, Sheril; Lo, Mischelle; Jovina, Jovina (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The work agreement is a form of agreement between the first party (company) and the second (labor) in carrying out a work relationship. Work agreements according to the labor law are PKWT and PKWTT. This also applies to PT. Angkasa Engineers Indonesia who enters into work agreements in accordance with applicable laws. This company also has a work agreement form PKWT and PKWTT. This study aims to determine the application of a specified time employment agreement (PKWT) at PT. Angkasa Engineers Indonesia. The results of this study indicate that the implementation of work agreements at PT. Angkasa Engineers Indonesia is deemed to have complied with the provisions of law No. 11 of 2020, Law No. 13 of 2003 concerning manpower. In this case, it can be seen from the contents of the work agreement that has been discussed and there is no trial period in a matter of months. In terms of wages, it is also in accordance with Article 58 paragraphs 1 and 2 of the 2003 Law on Manpower.